2017
DOI: 10.1021/acsami.7b12396
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast and Efficient Extraction of Uranium from Seawater Using an Amidoxime Appended Metal–Organic Framework

Abstract: Enrichment of uranyl from seawater is crucial for the sustainable development of nuclear energy, but current uranium extraction technology suffers from multiple drawbacks of low sorption efficiency, slow uptake kinetics, or poor extraction selectivity. Herein, we prepared the first example of amidoxime appended metal-organic framework UiO-66-AO by a postsynthetic modification method for rapid and efficient extraction of uranium from seawater. UiO-66-AO can remove 94.8% of uranyl ion from Bohai seawater within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
110
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(110 citation statements)
references
References 52 publications
(79 reference statements)
0
110
0
Order By: Relevance
“…[23,24] In order to obtain a deeper insight, it is necessary to perform X-ray adsorption experiments (XAS) to experimentally determine an accurate descriptiono ft he chromium local structure ando xidation state. [25][26][27][28] Nevertheless, it is worth noticing that XAS experimental technique is only availablea tl arge installation facilities, and that it fails to differentiate between different chromium speciesw hen ac omplex Cr VI ,C r V and Cr III mixture is found. Therefore, ap recise chromium speciation descriptionw ould require from the combination of specific techniques that allow i) distinguishing between the oxidation states of chromium ions and ii)obtaining information about the local structure of low concentrated chromium species.…”
Section: Introductionmentioning
confidence: 99%
“…[23,24] In order to obtain a deeper insight, it is necessary to perform X-ray adsorption experiments (XAS) to experimentally determine an accurate descriptiono ft he chromium local structure ando xidation state. [25][26][27][28] Nevertheless, it is worth noticing that XAS experimental technique is only availablea tl arge installation facilities, and that it fails to differentiate between different chromium speciesw hen ac omplex Cr VI ,C r V and Cr III mixture is found. Therefore, ap recise chromium speciation descriptionw ould require from the combination of specific techniques that allow i) distinguishing between the oxidation states of chromium ions and ii)obtaining information about the local structure of low concentrated chromium species.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Among these techniques, adsorption of uranium by using adsorbents appears to be the most effective owing to its high efficiency,low cost, and ease of operation. Adsorbents of different types have been developed for uranium extraction, including fibers, [9] hydrogels, [10] metal-organic frameworks, [11] porous organic polymers, [12] porous aromatic frameworks, [13] covalent organic frameworks, [14] and carbon materials. [15] Especially the amidoxime-based adsorbents,w hich contain the amidoxime chemical chelating functional group,i sh ighly promising for seawater uranium extraction owing to its high loading capacity,r elative high specificity,a nd fast adsorption rate to the uranyl ion in seawater.…”
mentioning
confidence: 99%
“…Its extraction capability satises the strict commercial standard set by the economic evaluation of uranium extraction from seawater (UES) in 21 days, with total capacity of 6 mg g À1 and a service life of 10 adsorptiondesorption cycles (3% loss per cycle). The PAF adsorbents are superior to AO-UHMWPE-1 (2.93 mg g À1 ), 8 UiO-66-AO (2.68 mg g À1 ), 26 MIL-101-OA (4.61 mg g À1 ), 27 PVC-co-CPVC (5.22 mg g À1 ), 28 and ORNL (3.3 mg g À1 ). 29 Our techno-economic analysis showed that the use of inexpensive raw materials (biphenyl, nitrile, aluminium chloride, etc.)…”
Section: Resultsmentioning
confidence: 94%